PERANCANGAN SISTEM INFORMASI AKUNTANSI DENGAN METODE DECISION SUPPORT SYSTEM (DSS) - Dony Waluya Firdaus; Lina Rosalina; Hery Dwi Yulianto (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
The research was conducted at PT. Sinkona Indonesia Lestari is a manufacturing company engaged in the industry that produces quinine salt of quinine and its derivatives. The Company requires cash flow of financial statements information that is fast, precise, accurate and up to date for management decision making. Authors are interested with the title "Accounting Information System Design Method With Decision Support System (DSSâ€). Design studies using primary data and secondary data, system development methodology using output oriented methodology, process oriented methodology and the data oriented methodology. While the structure of system development used by the authors is Waterfall. Accounting information system design using a context diagram, data flow diagrams, system flowcharts, and Entity Relationship Diagram. With accounting information systems managers can improve the quality of decision making.